2001
DOI: 10.1002/1097-4644(20010401)81:1<56::aid-jcb1023>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of PCNA to sites of DNA replication in the mammalian cell nucleus*

Abstract: We have examined the targeting of proliferating cell nuclear antigen (PCNA), an integral component of the mammalian replicative enzyme DNA polymerase delta, with sites of DNA replication by using confocal microscopy and computer image analysis. Labeling (5 min pulse) of DNA replication sites in normal human diploid fibroblast cells (NHF1) with BrdU was followed by immunostaining with PCNA antibodies. A striking degree of colocalization was seen between PCNA and the characteristic patterns of DNA replication si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 56 publications
(65 reference statements)
3
47
0
Order By: Relevance
“…It has been shown that enzymes required for DNA replication are concentrated into similar granules during S-phase (57). One of these enzyme is PCNA, and both immunostained PCNA and EGFP-tagged PCNA have been shown to be concentrated into replication foci (58,59). As shown in Fig.…”
Section: Characterization Of Parp-1-dsred and Topo I-eyfp-tomentioning
confidence: 87%
“…It has been shown that enzymes required for DNA replication are concentrated into similar granules during S-phase (57). One of these enzyme is PCNA, and both immunostained PCNA and EGFP-tagged PCNA have been shown to be concentrated into replication foci (58,59). As shown in Fig.…”
Section: Characterization Of Parp-1-dsred and Topo I-eyfp-tomentioning
confidence: 87%
“…51,52 Remarkably, a fraction of p21 wt GFP was found to be chromatinbound, and to co-localize with PCNA recruited to detergent-insoluble chromatin. The cell cycle position of the majority of GFP-expressing cells, as determined by PI staining, showed that these cells had a G 1 -phase DNA content, thus indicating that PCNA bound to chromatin was actually at the G 1 /S phase transition, i.e., when replication proteins like PCNA, are assembled at DNA replication sites, 46,47,53 before DNA synthesis starts. This result was confirmed by the percentage of cells showing a detectable expression of cyclin A in p21GFP positive cells, in agreement with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…45 The latter is the form directly involved in the DNA replication process. 46,47 However, a direct proof that p21 can bind PCNA recruited to DNA replication sites, and the mechanism by which this interaction interferes with DNA synthesis in vivo, are still missing. In this study we have induced expression of a p21GFP fusion protein and analysed its ability to interact and co-localize with PCNA at DNA replication sites.…”
Section: Introductionmentioning
confidence: 99%
“…Because end resection and HR are activated mainly after cells enter the S phase, we specifically monitored the recruitment of CtIP to DSBs in S phase cells. We co-expressed RFP-PCNA with EGFP-CtIP alleles, and S phase cells are marked by PCNA foci (31). A series of N terminus CtIP deletion mutants including CtIP 45-897, CtIP 75-897, and CtIP 135-897, which are defective in CtIP dimerization, were examined, and all of these mutants are significantly impaired in localizing to DSBs (Fig.…”
Section: Ctip Dimerization Mutants Are Impaired In Hr-mediated Dsb Rementioning
confidence: 99%